Ultra-high-capacity wireless communication by means of steered narrow optical beams - Koonen, Ton (Philos Trans A Math Phys Eng Sci, 2020)
The optical spectrum offers great opportunities to resolve the congestion in radio-based communication, aggravated by the booming demand for wireless connectivity. High-speed infrared optical components in the 1500 nm window have reached high levels of sophistication and are extensively used already in fibre-optic networks. Moreover, infrared light beyond 1400 nm is eye-safe and is not noticeable by the users. Deploying steerable narrow infrared beams, wireless links with huge capacity can be established to users individually, at minimum power consumption levels and at very high levels of privacy. Fully passive diffractive optical modules can handle many beams individually and accurately steer narrow beams two-dimensionally by just remotely tuning the wavelength of each beam. The system design aspects are discussed, encompassing the beam-steering transmitter, wide field-of-view optical receiver and the localization of the user's wireless devices. Prototype system demonstrators are reported, capable of supporting up to 128 beams carrying up to 112 Gbit s(−1) per beam. Hybrid bidirectional systems which use a high-speed downstream optical link and an upstream radio link at a lower speed can provide powerful asymmetric wireless connections. All-optical bidirectional beam-steered wireless communication will be able to offer the ultimate in wireless capacity to the user while minimizing power consumption. This article is part of the theme issue ‘Optical wireless communication’.